Leptin and adiponectin receptor expression in oesophageal cancer. Issue 6 (24th March 2014) - Howard, J M; Cathcart, M C; Healy, L; Beddy, P; Muldoon, C; Pidgeon, G P; Reynolds, J V
Abstract: Background: Oesophageal adenocarcinoma is an exemplar model of an obesity-associated adenocarcinoma. Altered secretion of adipokines by visceral fat is believed to play a key role in tumorigenesis. This study examined leptin receptor (ObR) and adiponectin receptor (AdipoR1 and AdipoR2) expression in oesophageal cancer, and its relationship with patient obesity status, clinicopathological data and patient survival. Methods: Tissue microarrays were constructed from paraffin-embedded oesophagectomy specimens. ObR, AdipoR1 and AdipoR2 expression was quantified by immunohistochemistry. Anthropometric data were measured at the time of diagnosis, and obesity status was assessed using visceral fat area determined by computed tomography and body mass index. Receptor expression was correlated with various clinicopathological and anthropometric variables. Patient survival was estimated using the Kaplan–Meier method, and results compared between those with low versus high receptor expression. A Cox multivariable regression model was used to assess the relationship between survival and a number of co-variables. Results: All 125 tumours analysed expressed AdipoR1 and AdipoR2, whereas 96·8 per cent expressed ObR. There was no significant difference in tumour pathological features or patient obesity status between tumours with low versus high ObR expression. A high level of AdipoR1 expression was significantly associated with increased patient age, obesity and less advanced tumour (T) category. Expression of AdipoR2 was inversely associated with T category ( P = 0·043). Low AdipoR1 expression was an independent predictor of improved overall survival (hazard ratio 0·56, 95 per cent confidence interval 0·35 to 0·90; P = 0·017). Conclusion: The association between adiponectin receptor expression, obesity status and tumour category and survival suggests a potential mechanism linking obesity and oesophageal cancer. Abstract : Linking obesity to oesophageal cancer